Oral administration of Debaryomyces hansenii CBS8339-β-glucan induces trained immunity in newborn goats. (April 2020) - Angulo, Miriam; Reyes-Becerril, Martha; Cepeda-Palacios, Ramón; Angulo, Carlos
Abstract: Beta-glucans from yeast can induce trained immunity in in vitro and in vivo models. Intraperitoneal doses of β-glucans in mammals have shown to induce trained immunity, but the training effects of orally administering β-glucans are unknown. Newborn goats are susceptible to infections in the neonatal stage, so the induction of trained immunity could improve animal survival. This study aimed to describe the in vitro effects of immunological training by β-glucan from Debaryomyces hansenii (β-Dh) on caprine monocytes, as well as its in vivo effects using oral doses on newborn goats upon challenge with lipopolysaccharide (LPS). Hence in vitro, goat monocytes trained with β-Dh up-regulated the gene expression of macrophage surface markers (CD11b and F4/80) whereas enhanced cell survival and high phagocytic ability was found upon LPS challenge. In the in vivo experiment, newborn goats stimulated with two doses (day −7 and - 4) of β-Dh (50 mg/kg) and challenged (day 0) with LPS showed an increase in respiratory burst activity, IL-1β, IL-6, and TNFα production in plasma, and transcription of the macrophage surface markers. This study has demonstrated for the first time that trained immunity was induced with oral doses of β-glucan upon LPS challenge in mammals using newborn goats. Highlights: Training immunity by β-glucan from D. hansenii (β-Dh) up-regulated gene expression of goat macrophage surface markers. Goat monocytes trained with β-Dh enhanced cell survival and phagocytic ability upon LPS challenge. Oral administration of β-Dh to newborn goats increased cytokine production and transcription of macrophages surface markers. Oral administration of β-Dh can induce trained immunity in mammals.